Coexistence of acute fatty liver of pregnancy, gestational diabetes insipidus, and preeclampsia leading to severe hypernatremia and perinatal mortality: a case report - Chaudhary, Mamta Kumari; Gupta, Monish; Arora, Aashima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Acute fatty liver of pregnancy (AFLP) and gestational diabetes insipidus (GDI) are rare but life-threatening obstetric complications. AFLP is linked to hepatic dysfunction, which can impair the breakdown of placental vasopressinase, leading to GDI and eventually hypernatremia. The coexistence of AFLP with GDI can be further worsened by placental dysfunction associated with preeclampsia, due to the disruption of the placental barrier that allows fetal vasopressin to enter the maternal circulation. This rare confluence of AFLP, GDI, and preeclampsia is scarcely reported and presents significant diagnostic and management challenges. We report a 25-year-old G2P1 woman, at 36 weeks of pregnancy, presenting with fever, jaundice, altered mentation, and hypertension. Laboratory tests showed hypernatremia (195 mEq/l), low urine osmolality, and abnormal kidney and liver function tests. Swansea criteria confirmed AFLP. Sodium was gradually corrected at a rate of 6-8 mEq/l per day, and vaginal delivery was planned. A live baby weighing 2.08 kg was delivered but died from respiratory failure on day two. Maternal recovery was complete by day 11 postpartum. This case highlights the interaction between AFLP, preeclampsia, and GDI. It emphasizes the importance of careful sodium correction and increased suspicion of vasopressinase dysfunction in cases of unexplained hypernatremia.